2021
DOI: 10.1101/2021.05.20.21257512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Sars-Cov-2 IgA And IgG In Human Milk After Vaccination Is Dependent On Vaccine Type And Previous Sars-Cov-2 Exposure: A Longitudinal Study

Abstract: Importance: Limited data are available on COVID-19 vaccine impact in lactating women. Objective: To evaluate the impact of different COVID-19 vaccines on specific anti-SARS-CoV-2 IgA and IgG levels in human milk. Design, Settings and Participants: In this prospective observational study in Spain, 75 lactating women from priority groups receiving vaccination against SARS-CoV-2 were included (January to April 2021). Human milk samples were collected at seven-time points. A group with confirmed SARS-CoV-2 infecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…Furthermore, in another study of 84 lactating women, milk IgA secretion was observed 2 weeks after vaccination with the first dose of Pfizer-BioNTech vaccine while IgG secretion was observed a week after the administration of the second dose (Perl et al, 2021). In agreement with a previous study (Selma-Royo et al, 2021) our results revealed that while both vaccines increased milk anti-SARS-CoV-2 IgA levels, Pfizer-BioNTech induced higher IgG levels than Astra Zeneca vaccine after administration of the 2 nd dose. Moreover, mRNA-based vaccines induced their maximum effect after the administration of the 2 nd dose.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in another study of 84 lactating women, milk IgA secretion was observed 2 weeks after vaccination with the first dose of Pfizer-BioNTech vaccine while IgG secretion was observed a week after the administration of the second dose (Perl et al, 2021). In agreement with a previous study (Selma-Royo et al, 2021) our results revealed that while both vaccines increased milk anti-SARS-CoV-2 IgA levels, Pfizer-BioNTech induced higher IgG levels than Astra Zeneca vaccine after administration of the 2 nd dose. Moreover, mRNA-based vaccines induced their maximum effect after the administration of the 2 nd dose.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are concordant with previously reported increases in breastmilk SARS-CoV-2-specific IgA and IgG levels within a week after the second vaccine dose ( 10 , 11 , 27 , 28 ). SARS-CoV-2 specific IgA in the breastmilk reportedly achieved maximal levels a week after the second dose, where SARS-CoV-2-specific IgG was only evident 1 week after the second dose ( 12 , 14 , 28 31 ). The persistence of neutralizing activity up to 3 weeks post dose 2 corresponds to the continued elevation in SARS-CoV-2 RBD-specific IgG1 but not IgA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Then, BM was collected using a sterile pump in sterile bottles to normalize the milk collection. Samples included in the analysis were collected 15-20 days after the second dose of SARS-CoV-2 vaccine when the maximum immunological response in terms of antibody production has been reported (13)(14)(15). Samples were kept at -20°C until transferred to the laboratory where they were stored at -80°C until further analysis.…”
Section: Study Design and Volunteersmentioning
confidence: 99%
“…Samples were diluted 1:4 before analysis and a standard curve was included in each plate to facilitate the analysis of the immunoglobulin levels. The standard curve consisted in ten 3fold serial dilutions from a mixture of samples (n = 10) that had been tested in previous studies (13,14), and showed higher levels of both Ig concentrations. These milk samples were collected from mothers vaccinated against SARS-CoV-2 at 20 days after the second dose since a previous study showed higher levels of antibodies in that period (14).…”
Section: Breast Milk Sars-cov-2-speci C Antibody Detectionmentioning
confidence: 99%